Chromomeres, Topologically Associating Domains and Structural Organization of Chromatin Bodies in Somatic Nuclei (Macronuclei) of Ciliates - Vladimir Popenko; Pavel Spirin; Vladimir Prassolov; Olga Leonova (Frontiers in Bioscience-Landmark)
Background: In the twentieth century, the textbook idea of packaging genomic material in the cell nucleus and metaphase chromosomes was the presence of a hierarchy of structural levels of chromatin organization: nucleosomes – nucleosomal fibrils –30 nm fibrils – chromomeres – chromonemata – mitotic chromosomes. Chromomeres were observed in partially decondensed chromosomes and interphase chromatin as ~100 nm globular structures. They were thought to consist of loops of chromatin fibres attached at their bases to a central protein core. However, Hi-C and other related methods led to a new concept of chromatin organization in the nuclei of higher eukaryotes, according to which nucleosomal fibrils themselves determine the spatial configuration of chromatin in the form of topologically associating domains (TADs), which are formed by a loop extrusion process and are regions whose DNA sequences preferentially contact each other. Somatic macronuclei of ciliates are transcriptionally active, highly polyploid nuclei. A feature of macronuclei is that their genome is represented by a large number of “gene-sized” (~1–25 kb) or of “subchromosomal” (~50–1700 kb) size minichromosomes. The inactive macronuclear chromatin of “subchromosomal” ciliates usually looks like bodies 100–200 nm in size. The aim of this work was to find out which of the models (chromomeres or TADs) is more consistent with the confocal and electron microscopic data on structural organization of chromatin bodies. Methods: Macronuclear chromatin of four “subchromosomal” ciliate species (Bursaria truncatella, Paramecium multimicronucleatum, Didinium nasutum, Climacostomum virens) was examined using electron microscopy and confocal microscopy during regular growth, starvation and encystment. Results: Chromatin bodies ~70–200 nm in size observed in the interphase macronuclei consisted of tightly packed nucleosomes. Some of them were interconnected by one or more chromatin fibrils. Under hypotonic conditions in vitro, chromatin bodies decompacted, forming rosette-shaped structures of chromatin fibrils around an electron-dense centre. When the activity of the macronucleus decreased during starvation or encystment, chromatin bodies assembled into chromonema-like fibrils 100–300 nm thick. This data allows us to consider chromatin bodies as analogues of chromomeres. On the other hand, most likely, the formation of DNA loops in chromatin bodies occurs by the loop extrusion as in TADs. Conclusions: The data obtained is well explained by the model, according to which the chromatin bodies of ciliate macronuclei combine features inherent in both chromomeres and TADs; that is, they can be considered as chromomeres with loops packed in the same way as the loops in TADs.